2011
DOI: 10.1063/1.3607969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ion solvation on phase equilibrium and interfacial tension of liquid mixtures

Abstract: We study the bulk thermodynamics and interfacial properties of electrolyte solution mixtures by accounting for electrostatic interaction, ion solvation, and inhomogeneity in the dielectric medium in the mean-field framework. Difference in the solvation energy between the cations and anions is shown to give rise to local charge separation near the interface, and a finite Galvani potential between two coexisting solutions. The ion solvation affects the phase equilibrium of the solvent mixture, depending on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 37 publications
1
58
0
Order By: Relevance
“…The PB theory predicts a monotonic decrease of f s that scales approximately with (c b ) −1/2 , which arises from the electric field contribution in the free energy due to the surface charge. 41,42 With the inclusion of image charge interaction, our theory shows that f s changes nonmonotonically. At low salt concentration (c b < 10 −3 M), f s calculated by our theory follows closely the PB result; this is because the region affected by the image charge repulsion is relatively narrow compared to the screening length, giving a relatively small contribution to the surface excess energy when integrated over the entire solution.…”
Section: B With Symmetric Saltmentioning
confidence: 99%
“…The PB theory predicts a monotonic decrease of f s that scales approximately with (c b ) −1/2 , which arises from the electric field contribution in the free energy due to the surface charge. 41,42 With the inclusion of image charge interaction, our theory shows that f s changes nonmonotonically. At low salt concentration (c b < 10 −3 M), f s calculated by our theory follows closely the PB result; this is because the region affected by the image charge repulsion is relatively narrow compared to the screening length, giving a relatively small contribution to the surface excess energy when integrated over the entire solution.…”
Section: B With Symmetric Saltmentioning
confidence: 99%
“…(6) reduces to dc ðrÞ=dr ¼ Àzl 0 =½"ðrÞr 2 by integrating once with respect to the radial distance r. This equation is to be solved together with Eqs. (7) and (8).…”
mentioning
confidence: 99%
“…However, recently it has been shown that the solvation energy of the salt ions can significantly affect the phase behavior [3,4] and interfacial properties of liquid mixtures [5][6][7][8]. For example, Ref.…”
mentioning
confidence: 99%
See 2 more Smart Citations